EVALUASI KONSISTENSI PROGRAM DAN KEGIATAN DALAM RKPD DAN PPAS DINAS PUPR KABUPATEN KARIMUN TAHUN 2017-2019 - Diky Budiman; Tiuridah Silitonga; Muhammad Thaha Yasin Ramadhan Thaha; Yurika Afrianita (Karimun University, 2022)
Consistency of planning and budgeting in programs and activities is a process of integrating and strengthening the preparation of plans and budgets in achieving development goals. Assessing the consistency of programs and activities between planning and budgeting at the PUPR Office of Karimun Regency, an analysis was carried out through the 2017-2019 RKPD and PPAS documents. The purpose of this study was to determine and evaluate the consistency of programs and activities in the RKPD and PPAS of the Karimun Regency PUPR Service in 2017-2019. The research method used is descriptive qualitative. The results of this study indicate that the consistency of programs and activities in planning and budgeting documents at the PUPR Office of Karimun Regency in 2017-2019 is in the very good category and there are only a few programs and activities that are not consistent between planning and budgeting, this happens because the results the evaluation did not achieve some of the planned objectives, there were budget limitations, lack of coordination between regional apparatus, adjustment of central government policies with regional governments, (emergency) circumstances that determine budget shifts between organizational units, between activities and between types of spending. The advice given is to increase the intensity of information and communication with higher levels of government, improve the quality of HR officers/planners in carrying out each proposed activity, improve knowledge of the apparatus involved in budgeting and increase commitment to maintain planning and budgeting consistency and increase the use of e-information technology. planning and e-budgeting. Keywords: Consistency, Planning, Budgeting Abstrak Konsistensi perencanaan dan penganggaran dalam program dan kegiatan merupakan proses keterpaduan dan penguatan penyusunan rencana dan anggaran dalam pencapaian tujuan pembangunan. Menilai konsistensi program dan kegiatan antara perencanaan dan penganggaran di Dinas PUPR Kabupaten Karimun dilakukan analisis melalui dokumen RKPD dan PPAS tahun 2017-2019. Tujuan dari penelitian ini adalah untuk mengetahui dan mengevaluasi konsistensi program dan kegiatan dalam RKPD dan PPAS Dinas PUPR Kabupaten Karimun tahun 2017-2019. Metode penelitian yang digunakan yaitu deskriptif kualitatif. Hasil dari penelitian ini menunjukan bahwa Konsistensi program dan kegiatan dalam dokumen perencanaan dan penganggaran di Dinas PUPR Kabupaten Karimun pada tahun 2017-2019 berada pada kategori sangat baik dan hanya ada beberapa program dan kegiatan yang belum konsisten antara perencanaan dan penganggaran, hal ini terjadi karena Hasil evaluasi tidak mencapai beberapa tujuan yang direncanakan, ada batasan anggaran, kurangnya koordinasi antar perangkat daerah, penyesuaian kebijakan pemerintah pusat dengan pemerintah daerah, keadaan (darurat) yang menentukan pergeseran anggaran antar unit organisasi, antar kegiatan dan antar jenis belanja. Saran yang diberikan yaitu meningkatkan intensitas informasi dan komunikasi dengan pemerintah yang lebih tinggi, meningkatkan kualitas Petugas SDM/perencana dalam melakukan setiap usulan kegiatan, perbaikan pengetahuan aparatur yang terlibat dalam penganggaran dan peningkatan komitmen untuk menjaga konsistensi perencanaan dan penganggaran serta meningkatkan pengunaan teknologi informasi e-planning dan e-budgeting. Kata Kunci: Konsistensi, Perencanaan , Penganggaran